STEM Learning Design with Literation-Based Pop-Up Book Media in Elementary Schools - Artobatama, Irman; Hastuti, Woro Sri; Zubaidah, Enny; Wibowo, Setiawan Edi (Jurnal Prima Edukasia, 2023)
This study aims to examine the stages of developing a STEM learning design with literacy-based Pop-Up Book media. Media-integrated instructional designs can facilitate students' mastery of the studied subject. The implementation of learning designs with creative media has not been widely applied during teaching and learning activities in class, especially in thematic learning with the 2013 curriculum. Pop-Up Book Media is creative media applied to literacy-based STEM learning designs in school. This study used a design-based research method. Data were collected through interviews, expert assessments, and questionnaires. Pop-Up Book media based on literacy has been designed to be implemented through STEM learning designs in elementary schools. Therefore this creative media can be applied by teachers in learning with the 2013 curriculum in elementary schools.